Multidrug-Resistant Salmonella spp. Isolated from Local Food Markets: Molecular Factors - Magthab, E. A.; Al-Bayati, Asmaa M. S. (Journal for Research in Applied Sciences and Biotechnology, 2023)
Antibiotic-resistant Salmonella spp. linked with food remains a primary concern globally as it is associated between animals and humans, causing foodborne illness and zoonotic diseases. One hundred Salmonella isolates out of 241 swab specimens taken from slaughtered chicken were identified and investigated for their antimicrobial susceptibility pattern. Ampicillin (62%), tetracycline (59%), amoxicillin-clavulanic acid (46%), trimethoprim-sulfamethoxazole (35%), and ceftriaxone (24%) were the drugs with the highest prevalence of impedance. At 12%, 11%, and 8%, respectively, resistance to ciprofloxacin, chloramphenicol, and azithromycin was very negligible. In order to assess the frequency of resistance genes, six different kinds of genes were examined in this research. The findings revealed that the proportion of these genes included in the survey were tetA (10%), blaCMY-2 (32%), dfrA7 (17%), tetC (20%), sul2 (25%) , and blaTEM-1 (47%).